Biomimetic fabrication of superhydrophobic loofah sponge: robust for highly efficient oil–water separation in harsh environments. Issue 43 (5th July 2018) - Yu, Mingguang; Lin, Binbin; Chen, Shangxian; Deng, Qianjun; Liu, Guang; Wang, Qing
Abstract : Oil/water separation has become an increasingly important field due to frequent industrial oily wastewater emission and crude oil spill accidents. Abstract : Oil/water separation has become an increasingly important field due to frequent industrial oily wastewater emission and crude oil spill accidents. Herein, we fabricate a robust superhydrophobic loofah sponge via a versatile, environmentally friendly, and low-cost dip coating strategy, which involves the modification of commercial loofah sponge with waterborne polyurea and fused SiO2 nanoparticles without the modification of any toxic low-surface-energy compound. The as-prepared loofah sponge showed excellent superhydrophobic/superoleophilic properties and exhibited robustness for effective oil–water separation in extremely harsh environments (such as 1 M HCl, 1 M NaOH, saturated NaCl solution and hot water higher than 95 °C) due to the remarkably high chemical stability. In addition, the as-prepared loofah sponge was capable of excellent anti-fouling, has self-cleaning ability and could act as the absorber for effective separation of surfactant-free oil-in-water emulsions. More importantly, the as-prepared loofah sponge demonstrated remarkable robustness against strong sandpaper abrasion and finger wipes, while retaining its superhydrophobicity and efficient oil/water separation efficiency even after more than 50 abrasion cycles. This facile and green synthesis approach presented here has the advantage of large-scale fabrication of a multifunctional biomass-based adsorbent material as a promising candidate in anti-fouling, self-cleaning, and versatile water–oil separation.